Determination of optimum load resistances of MQ-series gas sensor circuit for specific gas concentrations - Ajiboye Aye Taiwo; Opadiji Jayeola Femi Jayeola Femi; Ajayi Adebimpe Ruth; Popoola Joshua Olusogo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
MQ-series gas sensors are frequently used in gas concentration sensing owing to their high sensitivity and relatively cheap cost. Reportedly, both the sensor’s circuit sensitivity (?) and power dissipation (?? ) are functions of sensor circuit load resistance (?? ). However, there is no well-established standard method for determining ?? value that can simultaneously yield maximum sensor circuit sensitivity (??) and acceptable ?? for a given value of gas concentration. To obtain optimum ?? , the dependence of ? and ?? on ?? for a given gas concentration was thoroughly investigated. The model equations for determining ?, ?? and ?? at ?? (??,???) were derived and MQ-6 gas sensor’s response to its associated gases was used for demonstrating the proposed method. Variations of both ? and ?? with respect to ?? were investigated when each of the associated gases has concentration of 1000 ppm. The sensor circuit optimal ?? must satisfy the dual conditions of (i) S=?? and (ii) ?? < set threshold. Results obtained from the analysis revealed that the values of ??,??? were 20, 24, 64, 120, and 152 kΩ for liquefied petroleum gas (LPG), CH4, H2, alcohol and CO respectively, corresponding to sensor powers of 0.3125, 0.2589, 0.0977, 0.0521, and 0.0411 mW.